Pertanggungjawaban Perseroan Terbatas Sebagai Wajib Pajak Badan Dalam Pelaporan Pajak Secara Online - Mekar Satria Utama; Amir Junaidi; Ismiyanto Ismiyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to answer whether the tax reporting arrangements for Limited Liability Companies as corporate taxpayers are appropriate and optimally meet state revenues and the form of corporate responsibility for online tax reporting errors. Limited Liability Companies have tax responsibilities inherent in their position as a company. In practice, in the digital tax transition there are differences in perceptions regarding the implementation of tax reporting. The implication is that there is legal uncertainty due to this differentiation. A digital tax reporting model is needed that is able to accommodate the needs of the realm of practice to ensure legal certainty. This research is normative with primary and secondary legal materials processed through statutory, case and conceptual approaches. The results of the research show that the tax reporting arrangements for Limited Liability Companies as corporate taxpayers are not yet appropriate and meet state revenues optimally because there are still differences in the concept of regulation and application of digital tax. Meanwhile, the form of corporate responsibility for online tax reporting errors is classified into corporate responsibility and individual responsibility. This form of responsibility carries the threat of criminal sanctions attached to individuals as well as administrative responsibility for individual companies.